Reliability of the Test of Visual Perceptual Skills-4th Edition for people with schizophrenia - Shu-Chun Lee; En-Chi Chiu (PLoS ONE, 2025)
Background The Test of Visual Perceptual Skills-4th Edition (TVPS-4) is widely used for repeated measures of visual perception. This study aimed to examine the test-retest reliability, internal consistency, and practice effect of the TVPS-4 in people with schizophrenia receiving care in community psychiatric rehabilitation facilities. Methods A repeated assessment design was employed, involving 80 participants. Test-retest reliability was evaluated using the intraclass correlation coefficient (ICC) and Pearson’s r. Internal consistency was evaluated using Cronbach’s alpha (α). Minimal detectable change (MDC) values were calculated at 95%, 90%, and 80% confidence levels. The MDC% was determined based on the MDC with 95% certainty. Cohen’s d effect sizes and paired t-tests were utilized to assess the practice effect. Results The ICC and Pearson’s r of the overall scale were 0.93 and 0.95, respectively. The ICC and Pearson’s r of the seven subscales were 0.59–0.84 and 0.61–0.84, respectively. The α was 0.66–0.90 and 0.73–0.89 in the first and second assessment, respectively. The MDC95 (MDC%), MDC90, and MDC80 ranged from 4.7–16.3 (13.2–34.8%), 3.9–13.6, and 3.1–10.6, respectively. Cohen’s ds were 0.06–0.26 and paired t-test showed significant differences in scores of the overall scale and the four subscales (p <  0.05). Conclusion The TVPS-4 has acceptable test-retest reliability, satisfactory internal consistency, and trivial to small practice effect. The MDCs at different confidence levels can be used to interpret the score changes at a particular level of certainty for individuals with schizophrenia.